Answer:
(4t − 3) (t − 6)
Step-by-step explanation:
Using AC method:
Given a quadratic ax² + bx + c, find factors of ac that add up to b. Divide those factors by a and reduce. The denominators become the coefficients and the numerators become the constants.
Here, a = 4, b = -27, and c = 18.
ac = 4 × 18 = 72
Factors of 72 that add up to -27: -3 and -24
Divide factors by a: -3/4 and -24/4
Reduce: -3/4 and -6/1
So the factored expression is:
(4t − 3) (t − 6)
Answer:
5.131 × 10¹⁴ Hz
Step-by-step explanation:
<u>Planck relation</u>
![\large\boxed{E = hf}](https://tex.z-dn.net/?f=%5Clarge%5Cboxed%7BE%20%3D%20hf%7D)
where:
- E = Energy of the photon (J).
- h = Planck's constant (J · s).
- f = frequency of light produced (Hz).
Given values:
- E = 3.4 × 10⁻¹⁹ J
- h = 6.626 × 10⁻³⁴ J · s
Substitute the given values into the formula and solve for f:
![\implies 3.4 \times 10^{-19}=(6.626 \times 10^{-34})f](https://tex.z-dn.net/?f=%5Cimplies%203.4%20%5Ctimes%2010%5E%7B-19%7D%3D%286.626%20%5Ctimes%2010%5E%7B-34%7D%29f)
![\implies f=\dfrac{3.4 \times 10^{-19}}{6.626 \times 10^{-34}}](https://tex.z-dn.net/?f=%5Cimplies%20f%3D%5Cdfrac%7B3.4%20%5Ctimes%2010%5E%7B-19%7D%7D%7B6.626%20%5Ctimes%2010%5E%7B-34%7D%7D)
![\implies f=\dfrac{3.4}{6.626} \times \dfrac{10^{-19}}{10^{-34}}](https://tex.z-dn.net/?f=%5Cimplies%20f%3D%5Cdfrac%7B3.4%7D%7B6.626%7D%20%5Ctimes%20%5Cdfrac%7B10%5E%7B-19%7D%7D%7B10%5E%7B-34%7D%7D)
![\implies f=0.5131\times 10^{(-19-(-34))}](https://tex.z-dn.net/?f=%5Cimplies%20f%3D0.5131%5Ctimes%2010%5E%7B%28-19-%28-34%29%29%7D)
![\implies f=0.5131 \times 10^{15}](https://tex.z-dn.net/?f=%5Cimplies%20f%3D0.5131%20%5Ctimes%2010%5E%7B15%7D)
![\implies f=5.131 \times 10^{14}](https://tex.z-dn.net/?f=%5Cimplies%20f%3D5.131%20%5Ctimes%2010%5E%7B14%7D)
Answer:
c = 5
Step-by-step explanation:
We can find a, b, c by filling in values from the table into the equation:
17 = a(2²) +b(2) +c
32 = a(3²) +b(3) +c
53 = a(4²) +b(4) +c
__
There are numerous ways to solve 3 linear equations in 3 unknowns. We can use elimination.
Subtracting the first equation from each of the other two, we get ...
15 = 5a +b . . . . . . . . . note that c has been eliminated from the equations
36 = 12a +2b
Subtracting twice the first from the second gives ...
(12a +2b) -2(5a +b) = 36 -2(15)
2a = 6
a = 3
__
Now that we have a value for "a", we can "back substitute" into the equations to find "b" and "c".
Substituting this into 15 = ..., we get ...
15 = 5(3) +b
0 = b
And substituting for "a" and "b" in the first original equation gives ...
17 = 4(3) +c
5 = c
The value of c, the constant of the function, is 5.
Answer:
I think he can do 12 outfits.
Step-by-step explanation:
I hope this helps. Sorry if I am wrong, I am not the greatest at math.